2019
DOI: 10.4103/tp.tp_2_19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of Plasmodium vivax infection, from benign to severe malaria: A tertiary care prospective study in adults from Delhi, India

Abstract: Objective:Plasmodium vivax infection has been recognized to be a cause of severe malaria in recent time. We report findings from a prospective observational study aimed at analyzing the clinical spectrum, complications, and outcome of patients infected with P. vivax malaria.Materials and Methods:The study was conducted in a tertiary care hospital of Delhi over a period of 2 years. All adults hospitalized with P. vivax malaria, confirmed on peripheral smear and/or rapid diagnostic test, were included in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 12 publications
(18 reference statements)
5
26
1
Order By: Relevance
“…Even though elevations in urea over 50 mg/dL and severe anemia (hemoglobin below 7 gm/dL) were associated with severity, these were used to classify the infection as severe and cannot be used as predictors. Mortality occurred in 7% of vivax infections, much higher than reported estimates of 0.3% to 1.3% (10,11).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Even though elevations in urea over 50 mg/dL and severe anemia (hemoglobin below 7 gm/dL) were associated with severity, these were used to classify the infection as severe and cannot be used as predictors. Mortality occurred in 7% of vivax infections, much higher than reported estimates of 0.3% to 1.3% (10,11).…”
Section: Discussioncontrasting
confidence: 53%
“…Prospective studies have shown that severe disease occurs in approximately 23% to 42% of vivax malaria infections (10,11). Thrombocytopenia is the most common "severe" manifestation of vivax infection (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that hepatosplenomegaly is more frequent in severe malaria [30]. Young children during malaria attacks have lymphocyte infiltrations in hepatic sinusoids, hyperplasia of Kupffer cells, and deposits of malaria pigment [31].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral malaria is one of the most significant forms of severe malaria involving the two major pathogenesis processes, i.e., cytoadherence and immunogenic reactions. Most cases of cerebral malaria are due to P. falciparum infection, whereas P. vivax infection rarely causes cerebral malaria [3].…”
Section: Introductionmentioning
confidence: 99%